2015
DOI: 10.15241/hb.5.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Career Adaptability, Resiliency and Perceived Obstacles to Career Development of Adolescent Mothers

Abstract: In this article, the authors analyze ways of categorizing civilian occupations and employment data collected by the U.S. Census Bureau over 6 decades (1960-2010) with respect to six kinds of work (Holland's RIASEC classification), occupational titles used, employment and income. O*NET provided data for the 2010 census regarding employment and income. The authors discuss the distribution of employment changes over time and the examination of findings in relation to science, technology, engineering and mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Sing et al ( 26 ) stated that being married is a key obstacle to finding a better job, and Kalb et al ( 27 ) reported that teenage mothers usually have a narrow chance of finding a job, and have poorer health and a lower income compared with women who do not have children. In addition, Barto et al ( 28 ) maintained that challenges such as problems in studying, occupation and financial restrictions reduce the chances in life for teenage women. Since the teenage women do not have essential substructures to reach their goals and suffer from inadequate life skills, marriage should be delayed as long as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Sing et al ( 26 ) stated that being married is a key obstacle to finding a better job, and Kalb et al ( 27 ) reported that teenage mothers usually have a narrow chance of finding a job, and have poorer health and a lower income compared with women who do not have children. In addition, Barto et al ( 28 ) maintained that challenges such as problems in studying, occupation and financial restrictions reduce the chances in life for teenage women. Since the teenage women do not have essential substructures to reach their goals and suffer from inadequate life skills, marriage should be delayed as long as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Also, adolescents' resilience is related to coping strategies to deal with stress (Connor & Davidson, 2003) and higher levels of civic engagement and adaptive work behavior (Masten & Osofsky, 2010). Research shows that preadolescents' and adolescents' resilience is positively related to career adaptability, life satisfaction, and future orientation (e.g., Barto et al, 2015;Santilli et al, 2016). Ong et al (2006) reported that higher levels of resilience predicted a weaker association between positive and negative emotions, especially on stressful days, and that, over time, positive emotions function to assist resilient individuals to recover from and cope with daily stressful events.…”
Section: Resiliencementioning
confidence: 99%
“…Very few studies, however, have explored the relationship between hope and CDSE. Within the SCCT framework, it is reasonable to assume that hope serves as a personal factor that leads to individual differences in CDSE, as research has supported the influence of personal characteristics on CDSE, including personality traits (Bullock-Yowell, Andrews, & Buzzetta, 2011; Wang et al, 2006), core self-evaluation (Koumoundourou, Kounenou, & Siavara, 2012), optimism (Creed, Patton, & Bartrum, 2004), and resiliency (Barto, Lambert, & Brott, 2015). In particular, Lent et al (1994) contended that cognitive factors might affect individuals’ interpretation of their experiences and in turn their self-efficacy.…”
Section: Hopementioning
confidence: 99%